Aggregate Output, Capital, and Labor in the Post-War U.S. Economy - Daniel Levy (Economics Letters, 1990)
New estimates of an aggregate long-term production function for the post-war U.S. economy are reported. The results indicate that this long-term aggregate production function exhibits a slight but statistically significant increasing returns to scale. Since virtually all econometric growth studies assume constant returns to scale, my finding raises serious doubts about the validity of this common practice. I also find that since the war real output has become more sensitive to changes in capital and less sensitive to changes in labor. In particular, I show that the long-run capital and labor elasticities of real output are both in the range of 0.44–0.55. Similar estimates for the capital and labor elasticities of output from earlier studies covering pre-war and the inter-war periods are 0.25 and 0.75, respectively.
Keywords: E10; E22; E23; E24; E25; O30; O40; O47; O51; 330; Aggregate Production Function; Cobb-Douglas Production Function; Returns to Scale; Long-Term; Increasing Returns to Scale; LR Capital Elasticity of Output; LR Labor Elasticity of Output; Estimates of Technical Progress